Faculty-Undergraduate Course Curriculum Collaboration. Issue 2 (3rd April 2022) - Blithe, Sarah Jane; Fidelibus, Brian
Abstract: This paper describes a collaboration between one faculty instructor and seven undergraduate student collaborators. Together, the team designed a new college course. The analysis provides a practical way for educational leaders to challenge the authority of knowledge–engaging students in their education and motivating faculty to freshen their course materials and pedagogies. Such a move promotes creative and divergent thinking, student engagement, inclusivity in the classroom, and collaborative practices. The authors present the benefits realized for the instructor, student collaborators, and students taking the course, as well as a number of challenges and limitations to consider when conducting faculty-student collaborations.